A novel ion imprinted SiO2 microsphere for the specific and rapid extraction and pre-concentration of ultra-trace methyl mercury. Issue 46 (21st April 2016) - Jiang, Wenjing; Chen, Zhiqiang; Cheng, Xian; Wu, Weihua; Wu, Yongning; Xu, Liangjun; Fu, FengFu
Abstract : A novel MeHg ion imprinted silica microsphere was designed and synthesized for the specific, cost-effective and rapid pre-concentration of ultra-trace MeHg from natural water. Abstract : To extract and pre-concentrate ultra-trace methyl mercury (MeHg) from natural water, a novel MeHg ion imprinted silica microsphere (MeHg IISM) was designed and synthesized by using silica microspheres as a supporting material, the complex ion of 1-pyrrolidinecarbodithioic acid and MeHg (PDC–CH3 Hg + ) as a template, methacrylic acid (MAA) as a functional monomer, azodiisobutyronitrile (AIBN) as an initiator, trimethylolpropane trimethacrylate (TMPTM) as a cross-linking agent and ethanol as a solvent. The as prepared MeHg IISM is easy to fabricate with low cost, and has excellent stability, specificity and adsorption capacity. It can be used to specifically extract and pre-concentrate ultra-trace MeHg from natural water samples with a recovery of 92–105%, a intraday relative standard deviation (RSD, n = 5) <5%, a inter-day RSD ( n = 5) <7% and less interference of other ions within 30 min. The as prepared MeHg IISM can be repeatedly used more than 50 times with a 30 mg MeHg per gram adsorption capacity. Combined with ICP-MS, it can be used for the rapid and cost-effective detection of ultra-trace methyl mercury in natural water. The success of this study promises a valuable technique for rapid, low-cost extraction/pre-concentration and detection of ultra-trace methyl mercury in aqueous environments.